A substrate tagging and two-step enzymatic reaction strategy for large-scale synthesis of 2, 7-anhydro-sialic acid. (1st June 2019) - Li, Wanqing; Ghosh, Tamashree; Bai, Yuanyuan; Santra, Abhishek; Xiao, An; Chen, Xi
Abstract: A sialyltransferase acceptor tagging and two-step enzymatic reaction strategy has been developed for multigram-scale chemoenzymatic synthesis of 2, 7-anhydro- N -acetylneuraminic acid (2, 7-anhydro-Neu5Ac), a compound that can serve as a sole carbon source for the growth of Ruminococcus gnavus, a common human gut commensal. Different approaches of introducing hydrophobic UV-active tags to lactose as well-suited sialyltransferase acceptors have been explored and a simple two-step high-yield chemical synthetic procedure has been identified. The UV-active hydrophobic tag facilitates monitoring reaction progress and allows facile product purification by C18-cartridges. A two-step enzyme-catalyzed reaction procedure has been established to combine with C18 cartridge-based purification process for high-yield production of the desired product in multigram scales with the recycled use of chromophore-tagged lactoside starting material and sialoside intermediate. This study demonstrated an environmentally friendly highly-efficient synthetic and purification strategy for the production of 2, 7-anhydro-Neu5Ac to explore its potential functions. Graphical abstract: Image 1 Highlights: High-yield multigram synthesis and facile purification of 2, 7-anhydro-sialic acid. Demonstrated recycled use of chromophore-tagged lactoside and sialoside. Designed and synthesized several chromophore-tagged sialyltransferase acceptors. Improved protection group-free synthesis of a tagged sialyltransferase acceptor. Developed an environmentally free high-yield two-step enzyme reaction cycle.